Representation of Mental Health Issues in the Movie Not Okay - Nasya Fairuzya Ramadhani; Yudha Wirawanda (Penerbit Jurnal Indonesia, 2024)
In this study, researchers will discuss the issue of scenes that represent how mental health issues are presented in the film Not Okay. The method in this research is a descriptive study using a qualitative approach. The population of this research is all the characters from the film Not Okay. Danni Sanders, the main character in the film Not Okay, is the subject or sample of the research. Data is collected through cutscene analysis which represents mental health issues through conversations and scenes which will be divided into several categories. Apart from verbal communication, researchers will also analyze non-verbal cues such as facial expressions because they can also be used to convey implied messages. The result of this research is the film